Ohio Community Pharmacist Interest and Participation in Community-Clinical Linkages - Scott J Alexander; Natalie A DiPietro Mager (University of Minnesota Libraries Publishing, 2019)
Background: Community-clinical linkages have been promoted as a means to improve population health.  The community pharmacy is an ideal location for these partnerships to occur due to the expertise of the community pharmacist. While the need for these partnerships exists, there are limited data regarding community pharmacists' current participation in such programs. Objective: The purpose of this analysis was to assess Ohio community pharmacists' involvement and interest in community-clinical linkages.  Methods: An electronic survey tool containing 26 questions was developed to assess Ohio community pharmacists' participation in community-clinical linkages and interest to develop such partnerships. The tool was sent via email to a random sample of 500 pharmacists registered in Ohio and practicing in a community setting.  Chi-square or Fisher exact nonparametric statistical tests were used as appropriate to identify whether there were any significant differences in current partnership or interest to partner with a prescriber who refers patients to their community pharmacy based on education (Bachelor of Science or Doctor of Pharmacy degree) or pharmacy location (urban, suburban, or rural).  Results: Nine emails were undeliverable, leaving a sample of 491 pharmacists.  Ninety-three (19%) responded to the survey.  Sixteen respondents (17%) indicated that they currently partner with a prescriber who refers patients to their pharmacy for assistance with medications or chronic disease state management; this practice was more often reported in urban settings (p=0.022).  Of those not currently participating in such a partnership, 53 (57%) were interested in developing one.  Thirty-two respondents (34%) reported providing referrals for at least 1 type of screening or counseling service.  For some types of services, pharmacists reported that they provide the service in the pharmacy and/or were interested to develop the service in the pharmacy rather than provide a referral.  However, for any given service there were a number of pharmacists who expressed interest in providing referrals although they were not currently doing so. Conclusion: This sample of Ohio community pharmacists reported limited participation in community-clinical linkages but interest to develop them.  Further studies should explore the pharmacists' role and impact in such programs.   Article Type: Original Research